Islamic Finance And Environmental Sustainability: A Systematic Review On Green Sukuk And Esg In Sharia Economics - Jelita Juniarti (SHACRAL: Shari'ah Economics Review Journal, 2026)
The accelerating global transition toward low-carbon development has intensified demand for sustainable finance instruments aligned with both ethical principles and environmental objectives. Green sukuk, as a Sharia-compliant fixed-income instrument whose proceeds are designated for environmentally beneficial projects, has emerged as a critical innovation at the intersection of Islamic finance and the green finance movement. Concurrently, the integration of environmental, social, and governance (ESG) criteria into Islamic investment frameworks has generated significant academic and regulatory interest. Despite this growing attention, the scholarly literature on green sukuk and ESG within Islamic finance remains fragmented, spanning regulatory studies, market analyses, and conceptual discussions without a comprehensive synthesis. This study conducts a systematic literature review (SLR) of 54 peer-reviewed studies and institutional reports published between 2015 and 2024, examining the development, structure, regulatory frameworks, environmental impacts, and market challenges of green sukuk and ESG integration in Sharia economics. Employing qualitative thematic analysis, five major themes are identified: the structural and Sharia compliance dimensions of green sukuk; the integration of ESG criteria within Islamic finance screening frameworks; regulatory and governance architectures; environmental impact measurement and climate finance contributions; and market development challenges including standardization, liquidity, and investor awareness. Findings indicate that green sukuk and ESG-aligned Islamic finance demonstrate strong compatibility with both Maqashid al-Shariah and sustainable development objectives, while significant institutional and market barriers constrain their full potential. The study contributes a structured conceptual foundation for future empirical research and provides policy recommendations for policymakers, regulators, and Islamic financial institutions seeking to advance the environmental dimension of sustainable finance.